Enhancing Human-Robot Interaction in SMEs: Bridging Manual Workflows and Agile Automation - Muneeb, Iram (My University, 2025)
With rapid advancements in technologies, the demand for small and medium-sized enterprises to incorporate agile automation into their workflows has exponentially grown. The following study explores the research question that is “How can human–robot interaction (HRI) be designed and implemented in SMEs to ensure a smooth human-centred transition from manual workflows to agile automation?” The literature focuses on four main components, which are Human–Robot Interaction (HRI), Agile Automation (AA), Human-Centred Design (HCD), and Organisational Change. These components are critical for the successful deployment of automation in SMEs. Research also highlights that human-centered design (HCD), trust, safety, and worker involvement are all essential for successful HRI adoption. Conversely, current studies remain fragmented and rarely examine the human and organisational traits that influence how workers respond to collaborative robots (cobots) in real settings. The study applies a qualitative and exploratory approach based on the three experiments done under the ARISE project, which are RAPSEB, SUNRISE, and RISES. Thematic and comparative analysis driven by the Input–Process–Output (IPO) framework. The findings of these experiments reveal that an effective Human-Robot Interaction in small and medium enterprises is dependent on cultivating workers’ trust, effective communication through multimodal interfaces, ensuring human safety in shared workspaces, and supporting cognitive and organisational change. This study covers critical insights, limiting factors, and recommendations to encourage trust, enhance usability, and workers’ acceptance during the transition from manual to human-centered agile automation.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management